Host-Microbe-Pathogen Interactions: A Review of Vibrio cholerae Pathogenesis in Drosophila - Davoodi, Saeideh; Foley, Edan (Frontiers in Immunology, 2020)
Most animals maintain mutually beneficial symbiotic relationships with their intestinal microbiota. Resident microbes in the gastrointestinal tract breakdown indigestible food, provide essential nutrients, and importantly, act as a barrier against invading pathogens. For example, the enteric pathogen Vibrio cholerae must first overcome the barrier presented by commensal microbes prior to pathogenic colonization of intestinal niches. Over the last decades, our knowledge of V. cholerae pathogenesis, colonization, and transmission has increased tremendously. A number of animal models have been used to study how V. cholerae interacts with host-derived resources to support gastrointestinal colonization. Here, we review studies on host-microbe interactions and how infection with V. cholerae disrupts these interactions, with a focus on contributions using the Drosophila melanogaster model. We will discuss studies that highlight the connections between symbiont, host, and V. cholerae metabolism; crosstalk between V. cholerae and host microbes; and the impact of the host immune system on the lethality of V. cholerae infection. These studies suggest that V. cholerae modulates host immune-metabolic responses in the fly and improves Vibrio fitness through competition with intestinal microbes.